2022
DOI: 10.1002/jum.16029
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of Shear Wave Elastography With Shear Wave Dispersion Imaging in the Preoperative Evaluation of Hepatic Parenchyma in Patients With Liver Tumors

Abstract: Objectives This study aimed to compare the diagnostic accuracy of shear wave elastography (SWE) with that of shear wave dispersion (SWD) in evaluation of hepatic parenchyma in patients with liver tumors before resection. Methods A total of 174 patients with liver tumors were prospectively enrolled. SWE and SWD examinations were performed. Fibrosis stage and necroinflammatory activity were determined histopathologically according to the Scheuer standard. We compared the diagnostic accuracy of SWE and SWD. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…As a novel technique, there are few studies on SWD, and researchers are trying to explore what SWDS represents pathologically. Several published studies have suggested that SWDS may be related to the degree of hepatic inflammation and fibrosis [ 18 , 20 ]. The persistence of hepatic inflammation leads to fibrosis, which is an important factor associated with the development of PH.…”
Section: Discussionmentioning
confidence: 99%
“…As a novel technique, there are few studies on SWD, and researchers are trying to explore what SWDS represents pathologically. Several published studies have suggested that SWDS may be related to the degree of hepatic inflammation and fibrosis [ 18 , 20 ]. The persistence of hepatic inflammation leads to fibrosis, which is an important factor associated with the development of PH.…”
Section: Discussionmentioning
confidence: 99%
“…Using soft tissue as an example, whose properties are listed in Table 1, 49 the distribution of Rayleigh wave displacements in Equation (11) with increasing depth is shown in Figure 2. Be noted that the wave frequency (f) in this demonstration is chosen as 5 MHz.…”
Section: Rayleigh Wavementioning
confidence: 99%
“…4 By evaluating tissue elasticity, elastography techniques enable the diagnosis of lung diseases like pulmonary fibrosis, 5,6 pulmonary edema, 7 and emphysema, 8 as well as liver conditions such as fibrosis, 9 cirrhosis, 10 and hepatic tumors. 11 In renal disease, elastography aids in the early detection of subclinical renal fibrosis, 12 a major risk factor for chronic kidney disease, offering a valuable tool for preventive intervention. Pancreatic elastography holds promise in differentiating chronic pancreatitis from pancreatic tumors, potentially guiding treatment decisions with increased precision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the same authors demonstrated a moderate correlation between SWE and SWDS and inflammatory activity in a similar study comprising benign and malignant liver tumours (hepatocellular carcinoma, intrahepatic cholangiocarcinoma, mixed hepatocellular carcinoma-intrahepatic cholangiocarcinoma, and liver metastases), but multivariate analysis confirmed the absence of an association. Interestingly, they described a significantly higher LS and SWDS of liver parenchyma in primary liver cancer compared to other liver tumours [ 32 ].…”
Section: Clinical Studiesmentioning
confidence: 99%